MOTIVASI BRAZIL MELAKUKAN KERJASAMA PENGEMBANGAN BIOETANOL DENGAN INDONESIA TAHUN 2007 – 2012 - Deri Rahmadayani; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study used a qualitative research methods that the source datais taken from books , journals , newspapers , the internet , and previousstudies have data that is relevant to the title . Perspectives and levels ofanalysis used in this study is that the state as the main actor . By using thetheory of international cooperation and energy security , will explain thedirection of the object of analysis .This research will explain whatmotivated the Brazilian bioethanol develop cooperation with Indonesia in2007-2012 . This study to determine how the Brazilian bioethanol canbreak away from dependence on fossil fuels and break away from foreigndebt higher due to higher world oil prices . This study focused on how theBrazilian economy may emerge from the downturn as a result of relianceon petroleum world , how to make the Brazilian bioethanol as biofuel isenvironmentally friendly and be a commodity that is so promisingBrazilian exports of Brazil , and the success of Brazil became the worldleader in state develop bioethanol . This study will answer how Brazilseeks to enhance the role of trying to be a worldwide leader in cooperatingcountries - developed countries and countries - developing countries suchas Indonesia to Brazil's political and economic interests . It is theBrazilian strategy to increase its role in the world , Southeast Asia ,especially IndonesiaKeywords : Bioethanol , Cooperation , Policy , Energy Supply